The Tol-Pal System Plays an Important Role in Maintaining Cell Integrity During Elongation in Escherichia coli - Park, Sohee; Cho, Hongbaek (Frontiers in Microbiology, 2022)
The Tol-Pal system is a transenvelope complex widely conserved among Gram-negative bacteria. It is recruited to the septal ring during cytokinesis, and its inactivation causes pleiotropic phenotypes mainly associated with the division process. From our genetic screen to identify factors required for delaying lysis upon treatment of beta lactams, we discovered that the tol-pal mutant shares similar defects with mutants of the major class A PBP system (PBP1b-LpoB) in terms of lysis prevention. Further phenotypic analyses revealed that the Tol-Pal system plays an important role in maintaining cell integrity not only during septation, but also during cell elongation. Simultaneous inactivation of the Tol-Pal system and the PBP1b-LpoB system leads to lysis during cell elongation as well as during division. Moreover, production of the Lpo activator-bypass PBP1b, but not wild-type PBP1b, partially suppressed the Tol-Pal defect in maintaining cell integrity upon treatment of mecillinam specific for the Rod system, suggesting that the Tol-Pal system is likely to be involved in the activation of aPBP by Lpo factors. Overall, our results indicate that the Tol-Pal system plays an important role in maintaining cell wall integrity during elongation in addition to its multifaceted roles during cytokinesis.